The Potential of Phytochemicals in Oral Cancer Prevention and Therapy: A Review of the Evidence - Lee, Tzu-Ying (Biomolecules, 2020)
The etiological factors of oral cancer are complex including drinking alcohol, smoking tobacco, betel quid chewing, human papillomavirus infection, and nutritional deficiencies. Understanding the molecular mechanism of oral cancer is vital. The traditional treatment for patients with oral squamous cell carcinoma (e.g., surgery, radiotherapy, and chemotherapy) and targeted molecular therapy still have numerous shortcomings. In recent years, the use of phytochemical factors to prevent or treat cancer has received increasing attention. These phytochemicals have little or no toxicity against healthy tissues and are thus ideal chemopreventive agents. However, phytochemicals usually have low water solubility, low bioavailability, and insufficient targeting which limit therapeutic use. Numerous studies have investigated the development of phytochemical delivery systems to address these problems. The present article provides an overview of oral cancer including the etiological factors, diagnosis, and traditional therapy. Furthermore, the classification, dietary sources, anticancer bioactivity, delivery system improvements, and molecular mechanisms against oral cancer of phytochemicals are also discussed in this review.